Initiatives drawn for local skilled construction workers in Malaysia / Norazlin Mat Salleh … [et al.] - Mat Salleh, Norazlin; Hussien, Edelin; Syed Jamalulil, Syarifah Nur Nazihah; Muhammad, Nurul Huda; Ibrahim, Irma Hanie (2018)
High skilled human resources have become increasingly demanded and important by employers in Malaysia. However, it is become challenges in terms of the availability of local skilled labour to fulfil the vacancies in construction projects. Even thought there are substantial numbers of graduates and trainees produced by the Technical, Vocational education and Training (TVET) but employers are still reliance on unskilled foreign labour to work in construction site. Therefore, the objectives of research to provides an overview of Malaysian construction industry and to identify the initiatives has been planned to encourage local skilled labour to enter construction labour market. The commitments of the government were not isolated supported with industries on this issue and the improvement and enhancement for the young generation are unlimited. Currently, construction sector is including under key contributors to the Malaysian economics with services, manufacturing, mining and quarrying and agriculture. A review from various published documents to the present has been used to provide a comprehensive summary of literature on initiatives to raise the participation of local skilled construction workers to works at the construction site. Primarily, the initiatives can be divide into three main categories such as fund, education and technology. Such result indicates that, the initiatives are injection of fund by government, transforming and rebranding Technical and Vocational Education Training (TVET) especially construction based training programmed and the usage of high technology such as Integrated Building System (IBS) to reduced dependency on unskilled foreign workers. The initiatives identified by this research will form a basis for future research on the Malaysian construction industry